Comprehensive analysis of non-coding RNA-mediated endothelial cell-specific regulatory circuits in coronary artery disease risk - Huang, Boshui; Lai, Zhijie; Wang, Xiaoyu; Zhang, Qinhao; Hu, Tingting; Yu, Fulong; Zhou, Shuxian; Zhang, Yan; Meng, Juan (Frontiers in Genetics, 2025)
Coronary artery disease (CAD) remains the leading cause of mortality worldwide, driven by both lifestyle factors and genetic predisposition. Large-scale population genetic studies have greatly enhanced our understanding of the genetic underpinnings of CAD and facilitated the discovery of disease-associated genes. Noncoding RNAs, such as circular RNAs (circRNAs) and microRNAs (miRNAs), play crucial roles in the regulation of these genes. However, the impact of CAD-associated genetic variants on noncoding RNAs and their regulatory gene networks remain largely unexplored. In this study, we systematically identified the targets of both noncoding and coding genes influenced by CAD-associated variants. We constructed a CAD risk gene network, encompassing circRNAs, miRNA and genes, based on the concept of competing endogenous RNA regulation. Additionally, we focused on the endothelial cell (EC)-specific gene regulatory network to prioritize disease-associated circRNAs. Notably, we identified two CAD-associated variants that may disrupt circZNF609 and circABCC1, potentially altering their function as miRNA sponges and impacting EC-specific gene regulation, ultimately contributing to disease risk. Our findings link CAD genetic predisposition to noncoding RNA-mediated gene regulatory mechanisms in specific cell types, providing a valuable resource for novel target identification and advancing precision medicine in CAD.